The Relationship between Increased Transaminase Enzyme Levels on Severity and Mortality of COVID-19 Patients treated at RSUD Dr. Saiful Anwar Malang - Supriono Supriono; Nadina Zerlinda Mustamsir (Clinical and Research Journal in Internal Medicine, 2022)
Background: The involvement of the liver in COVID-19 is not yet well understood, but several studies have suggested an association between elevated liver transaminases and the severity and mortality of COVID-19. Aim: This study aims to analyze the liver enzyme profiles of COVID-19 patients and determine the correlation between the severity of COVID-19 with the risk of mortality. Methods: The study was an observational study with case-control analysis. It was conducted between August 1, 2020, and October 31, 2020. The samples were collected consecutively based on the order of hospitalized research subjects in RSUD dr. Saiful Anwar Malang, East Java, Indonesia and were handed by the department of internal medicine. RT-PCR was used to confirm the diagnosis of COVID-19. The collected and grouped data was presented in tabulated form, and statistical analysis was carried out using a non-parametric analysis test with the Chi-Square Test method. Results: The study found that 51.4% of patients had elevated AST (Aspartate transaminase) levels, and 41.8% had elevated ALT (alanine aminotransferase) levels. AST and ALT data showed the severity and mortality variable's probability value (p-value) was < 0.005. Conclusion: This study's results indicated a significant relationship between increased transaminase enzymes with the severity and mortality rate of COVID-19 patients.